Modeling effect of rock shape characteristics on run-out distribution of rockfalls - T. Yoshida; R. Nomura; Y. Tuda; I. Yoshida; K. Terada; S. Moriguchi (Soils and Foundations)
The aim of this study was to analyze and model the effect of rock shapes on the run-out distribution characteristics of rockfalls. To this end, we conducted a parametric study of rockfall simulations using the discrete element method, which is a numerical simulation method capable of directly representing rock shapes. The results indicated a strong correlation between the sphericity of rocks and the run-out distribution characteristics, expressed by two types of sphericity. Furthermore, we developed a regression model that can predict the run-out distribution using these two sphericities and the parameters of the calculation conditions as the explanatory variables. Although there is some room for improvement in terms of the developed regression model, it was confirmed that the relationship between the sphericity of rocks and the run-out distribution characteristics suggests the potential to enhance efficient rockfall risk assessments through numerical analysis.